GENDER EQUALITY IN EDUCATION - Uktamova Laziza Zafarjon kizi; Odiljonova Zeboxon Farxod kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines gender equality in education and workplaces, highlighting progress and persistent challenges. It emphasizes the role of education in reducing inequality and shows how equal opportunities contribute to social development, economic growth, and improved participation for all individuals.